POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG NOMOR 2 TAHUN 2020 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2020 TENTANG KEBIJAKAN KEUANGAN NEGARA DAN STABILITAS SISTEM KEUANGAN UNTUK PENANGANAN PANDEMI CORONA VIRUS DISEASE 2019 (COVID-2019) DAN/ATAU DALAM RANGKA MENGHADAPI ANCAMAN YANG MEMBAHAYAKAN PEREKONOMIAN NASIONAL DAN/ATAU STABILITAS SISTEM KEUANGAN MENJADI UNDANG-UNDANG DIKAITKAN DENGAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In the history of the development of democracy in Indonesia, state power institutions have changed their functions and duties according to each. The division of power between the legislative, executive and judiciary provides room for mutual cooperation (Checks and Balances). Seeing the current global situation, the world is currently working hard to face the Covid-19 Pandemic which was declared by theWorld Health Organizationas a pandemic in most countries around the world, including in Indonesia which has implications for social, economic and social welfare aspects. . By issuing Law No.2 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic and / or in the Context of Facing Threats Since the enactment of this Law, it has immediately drawn contra and criticism from various parties. and what is in the public spotlight on Law Number 2 of 2020 is inseparable from the existence of Article 27. TheThis type of research to be carried out is normative legal research which is also called doctrinal legal research. With literature review or literature study in searching the data using the deductive method. This research is descriptive in nature which provides data that is as thorough and detailed as the existing problems. In this paper, using qualitative data analysis, which means explaining and concluding about the data that has been collected by the author. through literature that investigates and makes an inventory of legal materials with documents, literature books, legal journals, and laws related to the object of research. From the results of the research and discussion it can be concluded that, First, the ratification of a Draft of Legislative Regulations into a Law is a form of mutual agreement between the President (Executive) and the House of Representatives (Legislative). Second, the implications of the birth of Law Number 2 of 2020. The author provides an ideal concept to the legislative body (which determines legal JOM Fakultas Hukum Universitas Riau Volume VIII No.2 Juli – Desember 2021 Page 2products) that should be closer to law than to politics itself for the sake of public welfare, not for unilateral benefits. It is also suggested that the formulation of legislation should be responsive and involve the community. Because the presence of law must always be adjusted to the development of the community. As a means of driving the progress of society because realistically in Indonesia today the function of the law does not work effectively, it is often manipulated, and even becomes an effective instrument for the accumulation of power. Keywords: Political Law - Formation of Law - Legislation of the DPR